Unravelling the mechanism of neurotensin recognition by neurotensin receptor 1 - Kazem Asadollahi; Sunnia Rajput; Lazarus Andrew de Zhang; Ching-Seng Ang; Shuai Nie; Nicholas A. Williamson; Michael D. W. Griffin; Ross A. D. Bathgate; Daniel J. Scott; Thomas R. Weikl; Guy N. L. Jameson; Paul R. Gooley (Nature Communications, 2023)
Abstract The conformational ensembles of G protein-coupled receptors (GPCRs) include inactive and active states. Spectroscopy techniques, including NMR, show that agonists, antagonists and other ligands shift the ensemble toward specific states depending on the pharmacological efficacy of the ligand. How receptors recognize ligands and the kinetic mechanism underlying this population shift is poorly understood. Here, we investigate the kinetic mechanism of neurotensin recognition by neurotensin receptor 1 (NTS1) using 19F-NMR, hydrogen-deuterium exchange mass spectrometry and stopped-flow fluorescence spectroscopy. Our results indicate slow-exchanging conformational heterogeneity on the extracellular surface of ligand-bound NTS1. Numerical analysis of the kinetic data of neurotensin binding to NTS1 shows that ligand recognition follows an induced-fit mechanism, in which conformational changes occur after neurotensin binding. This approach is applicable to other GPCRs to provide insight into the kinetic regulation of ligand recognition by GPCRs.